Menggugat pendidikan Indonesia : belajar dari Paulo Freire dan Ki Hajar Dewantara - Yamin, Moh., 1980- (Sleman, Jogjakarta : Ar-Ruzz Media, 2009)
Reforming educational system in Indonesia.
Includes bibliographical references (p. 283-290) and index.
Keywords: Freire, Paulo, -- 1921-1997.; Dewantara, Hadjar, -- 1889-1959.; Educational change -- Indonesia; Education and state -- Indonesia